A utilização de uma série de tv como suporte ao material de leitura para ESP: um estudo de caso - Jéssica Oliveira de Carvalho (2023)
Based on the observation of gaps regarding the scarcity of English for Specific Purposes (ESP) teaching materials in disciplines focused on the field of Health Sciences, this research aims to understand how excerpts from episodes of the American TV series Grey's Anatomy can enhance the teaching materials used in ESP reading practices in the Health Management Course at IFNMG - Araçuaí Campus. To achieve this objective, three specific aims were established: to identify and evaluate the main elements to be considered in the design of an ESP course, to produce ESP teaching materials focused on the development of specific text reading practices, including excerpts from Grey's Anatomy episodes, and to evaluate the learning experience with the produced material through a final questionnaire. The study in question consists of a qualitative research with a case study approach. It was carried out during the classes of the Technical English discipline, which is part of the Health Management Course at IFNMG. During the study, reading comprehension activities related to the health theme were developed, using the Grey's Anatomy series as a reference. The theoretical foundations of this study are based on Franco's (2018) research on the use of series in the teaching process and Ferreira's (2019) research on the relationship between language teaching and the use of television series. Regarding the concept of ESP and needs analysis, the research presented here is based on the assumptions presented by Hutchinson and Waters (1987); Dudley-Evans (2001); Anthony (2018); Soares (2018); among others. As for the need to produce teaching materials and resources for ESP, it is based on the contributions of Hyland (2006), Tomlinson (2011); Ulfa (2015); Marjanovikj-Apostolovski (2019); among other authors. Furthermore, the activities were based on pedagogical principles such as multiliteracies (COPE, KALANTZIS, 2000; ROJO, 2012; OLIVEIRA; SZUNDY, 2014), multimodality (COSCARELLI, NOVAIS, 2010; COSCARELLI, 2020; MARTINS, 2020), and digital literacy (COSCARELLI; RIBEIRO, 2014; SILVA, 2015; LACERDA; SANTOS, 2017). Data collection for this research was carried out through semi-structured questionnaires applied to students of the Health Management Course at IFNMG - Araçuaí campus. The data obtained were analyzed according to the content analysis proposal (CA) by BARDIN (2016). The results indicated that the didactic proposals were effective in promoting learning and developing students' language skills in the context of the Managing care course. Therefore, this study brings important contributions in the field of English for Specific Purposes, especially regarding the development of innovative teaching materials for the Health Management Course, which may arouse students' interest in the content to be studied in the course. Furthermore, teaching resources like this can be used by other educators in the same field, with due observations of the specificities of each learning group.